A New Underwater Acoustic Navigation Method Based on the Doppler Principle - Sen Zhang; Kun Fang; Jinsong Tang (Institute of Advanced Engineering and Science, 2014)
In this paper, a new underwater acoustic navigation method is proposed, which is named from Doppler Acoustic Omnirange Beacon (DAOB). It is borrowed from the idea of Doppler VHF Omnirange (DVOR) and based on the Doppler principle. The cause of Doppler effect in the received signal is the motion or position change of one or two sources. The effect of multipath is analyzed, and an improved signal form is presented to solve the rigorous multipath environment underwater. Some simulation is presented to verify the performance. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3968